(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2017)
Microbial community has been a major part in the drug industry. They are known for their effectiveness and do not cause any undesirable effects. Exploitation of bacteria could be fruitful for mankind. Bacteria play a major role in producing useful bioactive compounds. HSV-1 infection causes 80% of oral lesions. A majority of the population is infected by at least one herpes subtype of HSV-1 before adulthood. The infection in some cases does not produce any symptoms. Drugs for HSV-1 are becoming suppressive. In the present study, isolation of endophytic bacteria was carried out from medicinal plant. A grown bacterium was identified and confirmed using molecular 16S rRNA sequencing followed by extraction of bioactive compounds using solvents. Twelve bioactive compounds were then investigated for in vitro cytotoxicity assay and in vitro antiviral assay. Chloroform extract was found to be effective in inhibiting the virus.